Искатели приключений: рассказы / худож. И. Дербилова - Дербилова И. (Детвора, 2011)
Экземпляры: ф. 1 (20120411) / Инвентарный номер: 98516 / Цена: 183.38 / Сис.шифр: 84(2Рос=Рус) / Авт.знак: И 86 / ББК: 84(2Рос=Рус)